Repair of Oxidizing Hydroxyl Adduct Radicals of DNA Bases by Hydroxyl‐trans‐Stilbenes via Single Electron Transfer. Issue 13 (3rd April 2019) - An, Ping; Wang, Yuyue; Li, Shujin; Zhou, Liping
Abstract: Repair of oxidizing hydroxyl adduct radicals of DNA bases (base‐OH‐adduct) by eleven hydroxyl‐ trans ‐stilbenes via single electron transfer under physiological conditions are investigated using density functional theory. For eleven hydroxyl‐ trans ‐stilbenes (PSOHs), their anions make all the contributions to repairing oxidizing base‐OH‐adduct radicals. Ten PSOHs show better beneficial antioxidant effect than trans ‐resveratrol. 3, 3′, 4, 4′, 5, 5′‐Hexahydroxy‐ trans ‐stilbene (PSOH d ) performs the best repair activity to oxidizing base‐OH‐adduct radicals, and 3′, 4′, 5, 5′‐tetrahydroxy‐ trans ‐stibene has the smallest p K a value. The rate constants for the reactions of PSOH d with oxidizing base‐OH‐adduct radicals are about 10 5 ∼10 9  dm 3 mol −1 s −1 . Main factors affecting the repair reactions are the vertical ionization potential, the p K a of PSOHs and the vertical electron affinity of oxidizing base‐OH‐adduct radicals. This study gives information on repairing oxidizing base‐OH‐adduct radicals by PSOHs in biological environment for the first time and finds more beneficial antioxidant effect polyphenol than trans ‐resveratrol or piceatannol. Abstract : Repair of oxidizing hydroxyl adduct radicals of DNA base by eleven hydroxyl‐ trans ‐stilbenes via single electron transfer (SET) are investigated using density functional theory for the first time. Their anions make all the contributions to repairing oxidizing base‐OH‐adduct radicals. The rate constants for the reactions of PSOH d with oxidizing base‐OH‐adduct radicals are about 10 5 ∼10 9  dm 3 mol −1 s −1 .